ANOMALOUS CONTRIBUTIONS TO E+E- -] E+E-L+L- AT HIGH-ENERGIES - Almeida, L. D.; Eboli, OJP; Natale, A. A.; Novaes, Sérgio Ferraz [UNESP] (Springer, 1992)
We analyze the process e+ e- --> e+ e- gamma-gamma --> e+ e- l+ l- (l = e, mu, tau-leptons) considering several nonstandard contributions in order to search for new physics beyond the standard model. We are able to test compositeness up to the TeV mass scale at LEP II and CLIC energies.